PERANCANGAN ULANG TATA LETAK FASILITAS INDUSTRI YANG ADAPTIF PADA KONDISI PANDEMI COVID-19 (USAHA PELANGI FOOD KOTA BENGKULU) - alifah nurah fatonah; Meizul Zuki; Damres Uker (BPFP Faperta UNIB, 2022)
Many small enterprises especially engaged in the processing of agricultural products require a good arrangement of the layout of facilities. Pelangi Food is a small business that needs a good layout design to improve the smoothness of the production process during the pandemic. This study aims to obtain the initial layout state before the Covid pandemic at Pelangi Food, then obtain and implement a redesign of the facility layout during the pandemic using the 5S method (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) and the Covid-19 order and provide information on the advantages of redesigning the new industrial layout using the 5S method and the Covid-19 order. The methods used to redesign the layout of facilities in this study are the 5S method and the Covid-19 order. The results showed a) The layout of the initial industrial facilities was in poor condition and could not meet the level of needs of employees and consumers, b) Better layout of proposed facilities and meeting the level of needs of employees and consumers; changes in the use of storage space that is good and neatly arranged and there is no stacking of goods / products, grouping of good production tools and neat and orderly room arrangement, the work environment becomes neat, clean, safe and comfortable so that employees are more enthusiastic at work and consumers become more comfortable in shopping, and c) Innovation is able to improve the work environment that was originally in a bad condition and has not met the expectations of employees / consumers get better and be able to meet the expectations of employees and consumers.